2008
DOI: 10.1105/tpc.107.052043
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Synthesis inPhytophthora infestansIs Required for Normal Appressorium Formation and Successful Infection of Potato

Abstract: Cellulose, the important structural compound of cell walls, provides strength and rigidity to cells of numerous organisms. Here, we functionally characterize four cellulose synthase genes (CesA) in the oomycete plant pathogen Phytophthora infestans, the causal agent of potato (Solanum tuberosum) late blight. Three members of this new protein family contain Pleckstrin homology domains and form a distinct phylogenetic group most closely related to the cellulose synthases of cyanobacteria. Expression of all four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(171 citation statements)
references
References 63 publications
9
160
1
1
Order By: Relevance
“…Since the diploid nature of oomycetes hampers directed mutagenesis by gene disruption, we chose gene silencing as a method to obtain mutants. Gene silencing has been demonstrated in P. infestans and Phytophthora parasitica and was used for functional analysis of a few genes (7,20,22,52). For P. sojae, however, this is the first report describing successful silencing of a target gene.…”
Section: Discussionmentioning
confidence: 98%
“…Since the diploid nature of oomycetes hampers directed mutagenesis by gene disruption, we chose gene silencing as a method to obtain mutants. Gene silencing has been demonstrated in P. infestans and Phytophthora parasitica and was used for functional analysis of a few genes (7,20,22,52). For P. sojae, however, this is the first report describing successful silencing of a target gene.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of the latter, a single construct was made that was expected to silence PITG_09190, PITG_09198, PITG_09199, PITG_09200, and PITG_09201, since these exhibit about 96% sequence identity. Two prior studies in P. infestans have shown that single constructs can silence closely related genes (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…A feature usually mentioned when distinguishing oomycetes from true fungi is the presence of cellulose and the absence of chitin in their cell wall (40). This assumption stems from early studies mainly focused on the Phytophthora cell wall (6,7) and was recently reinforced by the demonstration that cellulose synthesis is required for normal appressorium formation in Phytophthora infestans (37). However, the cell wall of the closely related hyphochytridiomycetes contains both cellulose and chitin, and chitin was unambiguously detected by biophysical analyses in some oomycete species of the Leptomitale and Saprolegniale orders (2,12).…”
mentioning
confidence: 96%